ORIENTASI PASAR DAN INOVASI PRODUK TERHADAP KEUNGGULAN BERSAING (PADA PRODUK MIE INSTAN LEMONILO) - Damai Yanti (2023)
The sales value of instant noodles in Indonesia has continued to increase. Many companies create instant noodle products, one of which is Lemonilo. However, the sales revenue of Lemonilo instant noodles shows fluctuating conditions. So, it can be said that Lemonilo instant noodles unable to compete with other competitors. Thus, the formulation of the problem that has been determined is whether market orientation and product innovation affect competitive advantage. This study aims to determine, prove and analyze the effect of market orientation and product innovation on competitive advantage. The research population is all consumers of generation Z who have purchased or consumed Lemonilo instant noodle products in the DKI Jakarta area with a sample of 137 people using the non-probability sampling method and purposive sampling technique. Then, data analysis uses SmartPLS software. The results showed that market orientation was 0.594 and product innovation was 0.293 and had a positive and significant effect on competitive advantage in Lemonilo instant noodle products. The coefficient of determination explained by market orientation and product innovation is 57.9%. Meanwhile, the remaining 42.1% was caused by other factors, namely entrepreneurial orientation, perception and price level, product creativity, product quality, differentiation strategy, social media marketing, and others.